Graphene‐Based Nanocomposites for Energy Storage. Issue 16 (15th June 2016) - Ji, Liwen; Meduri, Praveen; Agubra, Victor; Xiao, Xingcheng; Alcoutlabi, Mataz
Abstract : Since the first report of using micromechanical cleavage method to produce graphene sheets in 2004, graphene/graphene‐based nanocomposites have attracted wide attention both for fundamental aspects as well as applications in advanced energy storage and conversion systems. In comparison to other materials, graphene‐based nanostructured materials have unique 2D structure, high electronic mobility, exceptional electronic and thermal conductivities, excellent optical transmittance, good mechanical strength, and ultrahigh surface area. Therefore, they are considered as attractive materials for hydrogen (H2 ) storage and high‐performance electrochemical energy storage devices, such as supercapacitors, rechargeable lithium (Li)‐ion batteries, Li–sulfur batteries, Li–air batteries, sodium (Na)‐ion batteries, Na–air batteries, zinc (Zn)–air batteries, and vanadium redox flow batteries (VRFB), etc., as they can improve the efficiency, capacity, gravimetric energy/power densities, and cycle life of these energy storage devices. In this article, recent progress reported on the synthesis and fabrication of graphene nanocomposite materials for applications in these aforementioned various energy storage systems is reviewed. Importantly, the prospects and future challenges in both scalable manufacturing and more energy storage‐related applications are discussed. Abstract : The recent overall status and progress of graphene and graphene‐based nanocomposites for energy storage devices, such as H2 storage, supercapacitors, Li‐ion batteries, Li‐S batteries, Li‐air batteries, Na‐ion batteries, Na‐air batteries, Zn‐air batteries, and vanadium redox flow batteries are summarized and discussed. The challenges, prospects, and potential development directions of these promising materials for advanced energy storage systems are also investigated.